CHALLENGES IN THE IMPLEMENTATION OF THE BUSINESS AUTOMATION PROJECT AT KENYA REVENUE AUTHORITY (KRA) A CASE OF KENYA REVENUE AUTHORITY - Atambo, Pantaleo; Katuse, Dr.Paul (European Journal of Business and Strategic Management, 2017)
Purpose:The purpose of this study was to determine the challenges encountered by KRA in implementation of business automation. Methodology:The research design was descriptive in nature and stratified random sampling technique was used to sample forty (40) respondents from a population of one hundred and fifty seven (157) staff working at KRA in the Information Communication and Technology department (ICT). The staff included both management and non-management staff. The study used both primary and secondary data. Primary data was collected using self administered questionnaires while secondary data sources comprised of internal memos, strategic plans, project plans and documentation relating to Business Automation activities. The data was then tabulated and weighted to determine key challenges and responses. The study used quantitative and qualitative methods of data analysis. Statistical Package for Social Sciences (SPSS) version 20 program was used for analysis. The results were presented using tables and pie charts. Similarly, qualitative data was summarized and categorized according to common themes and presented in continuous prose form. Results: The study concluded that organizational related challenges hindered implementation of business automation at KRA.The study also concluded that environmental related challenges hindered implementation of business automation at KRA. Further, the study concluded that better mitigation strategies enhance effective implementation of business automation projects in KRA Unique contribution to theory, practice and policy: The study recommends that KRA should deal effectively with the challenges highlighted above and implement their mitigation strategies.